Patient-Reported Outcomes in Metabolic Dysfunction-Associated Steatotic Liver Disease - Barberá, Aurora; White, Trenton M.; Arora, Anish K.; Henry, Linda; Lazarus, Jeffrey V.; Younossi, Zobair M. (Seminars in Liver Disease, 2024)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is the most common chronic liver disease worldwide and can progress to serious complications, including metabolic dysfunction-associated steatohepatitis (MASH), cirrhosis, end-stage liver disease, and hepatocellular carcinoma. Predisposing risk factors for MASH include obesity, type 2 diabetes, dyslipidemia, and metabolic syndrome. Patients with MASH often experience significant impairments in their health-related quality of life and other patient-reported outcomes (PROs), particularly in physical functioning domains, fatigue, and vitality. Incorporating PROs offers valuable insights into patients' perspectives on their symptoms, treatment efficacy, and overall well-being, thereby guiding more holistic and patient-centered care strategies. This review aims to investigate the utilization of patient-reported outcome measures (PROMs) in the context of MASLD and MASH care, identify which PROMs are employed, and summarize the outcomes reported.
Keywords: MASH; quality of life; MASLD; HRQoL; person-centered care